MERGER PERFORMANCE AND EFFICIENCIES IN HORIZONTAL MERGER POLICY IN THE UNITED STATES AND THE EUROPEAN UNION - KAMERBEEK, Sjoerd (Journal of Advanced Research in Law and Economics; Vol 1 No 1 (2010): JARLE Volume I Issue 1(1) Summer 2010, 2016)
In current horizontal merger policy in the US and the EU an explicit efficiency defense is allowed. On both sides of the Atlantic mergers are unconditionally approved if internal efficiencies are sufficient to reverse the mergers’ potential to harm consumers in the relevant market. Current merger policy is implicitly based on the assumption that rational managers will only propose privately profitable mergers. In this paper I will show that the empirical evidence on merger performance suggests that this assumption can’t be sustained. Managers do propose uneconomic mergers, motivated by non-wealth maximizing behavior. To tackle this problem I argue that efficiencies should not only be used as an efficiency defense, but efficiencies should work both ways. To avoid type I and type II errors the competition authorities in the US and the EU should undertake a sequential efficiency test in their assessment of specific mergers.
Keywords: merger, horizontal merger policy, X-inefficiency, Right Welfare Standard